The Opportunities for the Establishment of Madura Province: Weighing Capacities and Challenges - Moh Said; Cahyasari, Erlita (Journal of Governance Innovation, 2025)
This paper describes the opportunities for the establishment of Madura Province through an analysis of the capacities and challenges. The analysis is carried out on regional economy quality, equitable development, human resources quality, village development, fiscal capacity, and regional fiscal independence. Expanding regions or creating New Autonomous Regions is frequently the approach taken to enhance governance quality in the regions. Therefore, understanding the scope of the opportunities is crucial. The deepening of opportunities is achieved by analysing the capacities and challenges present in the new regional government. The results, it is known that the regencies on Madura Island have several advantages and challenges. The advantage is having GINI Index, HDI, and IDM ​​that are on average with regencies/cities in East Java. Meanwhile, the challenge is the quality of the regional economy as indicated by the GRDP, that is far below the regencies/cities in East Java. The following challenge is the region's limited capacity and fiscal independence. Compared to the values ​​of other regencies/cities in East Java, the capacity and fiscal independence of the four regencies on Madura Island are still below average. However, the quality of human resources, development, and existing equity can serve as the fundamental capital to maximize the management of the potential that is owned, if granted to become a province. Madura Island has sufficient natural resources and economic potential, with more authority, can be maximized and used to raise the standard of public services and governance, which will benefit the local society.